Why the Commercial Speech Doctrine Will Prove Toxic to the USDA National Organic Program - Heyman, Todd S. (Columbia Journal of Environmental Law, 2019)
This Article argues that the Supreme Court has expanded commercial speech rights too far. The current Court increasingly appears to view the government’s power to regulate commercial speech as limited to only proscribing false or misleading commercial speech. Any attempt by the government to restrict truthful commercial speech, even if potentially misleading, is generally treated as unjustified paternalism in violation of the First Amendment. The evolving jurisprudence threatens reasonable economic regulations that restrict speech for important and non-paternalistic reasons. To make this case, this Article explores how the evolving commercial speech doctrine could invalidate the food-labeling regime established by the Organic Foods Production Act of 1990 ("OFPA") and its implementing regulations. That regulatory regime, often referred to as the National Organic Program ("NOP"), generally prohibits representing food as "organic" unless a United States Department of Agriculture ("USDA") licensed inspector has certified that the food was produced consistent with OFPA’s implementing regulations. The National Organic Program: (1) provides assurance to the consumer that the product is indeed organic; (2) sets clear standards to define the organic market so that producers can enjoy a price premium for food produced consistent with those standards; and (3) incentivizes producers, through the price premium, to convert from conventional to organic production practices, resulting in substantial environmental benefits. Although the regulations facilitate the creation and growth of an organic market with integrity, the regulations are vulnerable to a First Amendment challenge because they restrict the use of the term "organic" to a very limited set of circumstances.